The Denitrification Characteristics and Microbial Community in the Cathode of an MFC with Aerobic Denitrification at High Temperatures - Zhao, Jianqiang; Wu, Jinna; Li, Xiaoling; Wang, Sha; Hu, Bo; Ding, Xiaoqian (Frontiers in Microbiology, 2017)
Microbial fuel cells (MFCs) have attracted much attention due to their ability to generate electricity while treating wastewater. The performance of a double-chamber MFC with simultaneous nitrification and denitrification (SND) in the cathode for treating synthetic high concentration ammonia wastewater was investigated at different dissolved oxygen (DO) concentrations and high temperatures. The results showed that electrode denitrification and traditional heterotrophic denitrification co-existed in the cathode chamber. Electrode denitrification by aerobic denitrification bacterium (ADB) is beneficial for achieving a higher voltage of the MFC at high DO concentrations (3.0–4.2 mg/L), while traditional heterotrophic denitrification is conducive to higher total nitrogen (TN) removal at low DO (0.5–1.0mg/L) concentrations. Under high DO conditions, the nitrous oxide production and TN removal efficiency were higher with a 50 Ω external resistance than with a 100 Ω resistance, which demonstrated that electrode denitrification by ADB occurred in the cathode of the MFC. Sufficient electrons were inferred to be provided by the electrode to allow ADB survival at low carbon:nitrogen ratios (≤0.3). Polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE) results showed that increasing the DO resulted in a change of the predominant species from thermophilic autotrophic nitrifiers and facultative heterotrophic denitrifiers at low DO concentrations to thermophilic ADB at high DO concentrations. The predominant phylum changed from Firmicutes to Proteobacteria, and the predominant class changed from Bacilli to Alpha, Beta and Gamma Proteobacteria.